One Major Challenge of Sequencing Large Plant Genomes Is to Know How Big They Really Are - Doležel, Jaroslav; Čížková, Jana; Šimková, Hana; Bartoš, Jan (International journal of molecular sciences, 2018)
Any project seeking to deliver a plant or animal reference genome sequence must address the question as to the completeness of the assembly. Given the complexity introduced particularly by the presence of sequence redundancy, a problem which is especially acute in polyploid genomes, this question is not an easy one to answer. One approach is to use the sequence data, along with the appropriate computational tools, the other is to compare the estimate of genome size with an experimentally measured mass of nuclear DNA. The latter requires a reference standard in order to provide a robust relationship between the two independent measurements of genome size. Here, the proposal is to choose the human male leucocyte genome for this standard: its 1C DNA amount (the amount of DNA contained within unreplicated haploid chromosome set) of 3.50 pg is equivalent to a genome length of 3.423 Gbp, a size which is just 5% longer than predicted by the most current human genome assembly. Adopting this standard, this paper assesses the completeness of the reference genome assemblies of the leading cereal crops species wheat, barley and rye.
Keywords: flow cytometry; Genome Size; Triticum; délka genomu; Genome, Plant; genom rostlinný; genom lidský; Sequence Analysis, DNA; standardization; sekvenční analýza DNA; pšenice; Genome, Human; referenční standardy; lidé; Humans; reference genome assembly; nuclear DNA content; Reference Standards; genome size